Role of marine sediments mineralogy in the study of magnetotactic bacteria - Cornaggia, Flaminia (2020)
Marine sedimentary minerals respond to modifications in the sedimentary environment, and thus can be representative of specific environmental and climatic conditions. The use of sedimentary mineralogical composition to reconstruct past and present environmental conditions has great potential, if used with the appropriate care. In this work, samples of marine sediments were analysed with X-Ray Powder Diffraction (XRPD) to characterize the mineralogical assemblages with focus on paleoceanographic reconstructions and characterization of environments in which magnetotactic bacteria (MTB) live. MTB are a heterogeneous group of gram-negative prokaryotes found in aquatic environments worldwide that internally biomineralize magnetic crystals called magnetosomes. Their presence has been linked to past events of global warming and high primary productivity, thus have a potential use as paleoceanographic proxies. Therefore, understanding the processes that link MTB to their environment is fundamental to constrain their ecology and use them efficiently as paleoenvironmental proxies. In particular, we present three case studies in which mineralogical data are integrated with magnetic properties, geochemical data, and statistical analyses. The first presents an abyssal setting (Tasman Abyssal Plain) with climate induced modifications at the 100ky scale during the Middle Eocene Climatic Optimum (MECO) event; the second addresses a lagoonal-estuarine environment (Cananeia, BR) with anthropic interference at the 100y scale; the third focuses on a recent ría environment (Mamanguá, BR) that can be considered stable at the annual to millennial time scales. In the former two cases, main environmental modification are recognized through the variations of mineralogical assemblages, whereas in the latter MTB thrive and no appreciable variations in the mineralogical composition occur. The study of the mineralogical composition of the sediments on the Tasman Abyssal Plain allowed us to confirm the occurrence of ocean acidification during the MECO and show that it even reached abyssal depths. Besides, this archive may yield the first evidence of Mn-doped magnetosomes in natural environments. The Cananeia case study reconstructed a lagoonal-estuarine environment, showing the response of sedimentary minerals to anthropic modifications. Although in all three case studies the presence of MTB is concomitant with an increase in the clay mineral fraction, data are not sufficient to clearly confirm a link between the presence of MTB and the mineralogical composition. MTB are a polyphyletic group and are found ubiquitous in aquatic environments, this implies that utmost care has to be used when correlating the general term MTB to a specific characteristic or ecologic preference. Many factors should be considered alongside the mineralogical composition of the environment, especially the specific taxonomy of the studied bacteria, which has not been possible to do in this study. As MTB consist of different taxa with different modes of life, a more extensive study in collaboration with biologists is necessary to select MTB communities well-defined form the taxonomical point of view, in order to determine the role of mineralogy in the ecological factors.